"Can I do this?" Multiracial student decisions to engage with racial justice student organizations at a historically White institution. Issue 174 (5th November 2021) - Malaney‐Brown, Victoria K.
Abstract: This article presents the voices of multiracial collegians at a Historically White Institution who make intentional choices to engage and disengage with racial justice student organizations.